Germline RECQL gene mutations in Chinese patients with breast cancer - Hu, Jun; Shen, Yong; Zhang, Kun; Chen, Yiding (Frontiers in Medicine, 2024)
Breast cancer is the most common malignant tumor in women, seriously threatening health and survival. TP-dependent DNA helicase Q1 (RECQL) is a breast cancer susceptibility gene with possible familial links. However, RECQL gene mutations among Chinese women with breast cancer have not been evaluated.Therefore, this study assessed RECQL mutations and their relationships with clinicopathological and epidemiological characteristics in Chinese women with breast cancer. We found that a RECQL mutation is a susceptibility factor for breast cancer.Moreover, patients with RECQL mutations were more likely to have a family history of breast cancer than those without. Also, patients with RECQL variants of uncertain significance (VUS) were less likely to develop invasive ductal carcinoma than those without. In addition, unexplained RECQL mutations occurred more often in patients with human epidermal growth factor receptor 2+ breast cancer than in those with other subtypes. These results provide a basis for creating screening criteria specific to Chinese women. However, the frequency of RECQL mutations was low, and the number of pathogenic mutations was too small and could not be analyzed. Thus, more extensive, long-term studies that include other functional experiments are needed to verify these results.